Open calcaneal fractures with medial wound: mid-term results - Sakaki, Marcos Hideyo; Missima, Kenji Maeda; Lima, Augusto César Rodrigues de; Pereira Bergamasco, Jordanna Maria; Cordeiro Filho, Gustavo Crespo; Martinez, Guilherme (Journal of the Foot & Ankle, 2023)
Objective: Present the clinical and radiographic results of a series of patients with open calcaneal fractures with medial wound. Methods: Retrospective study based on medical records of ten patients treated for open calcaneal fractures with medial wound from 2014 to 2020. All included patients had a minimum one-year follow-up. The variables analyzed were age, sex, laterality, associated diseases, mechanism of trauma, fracture according to Gustilo Anderson and Sanders classifications, associated fractures, surgeries performed, complications, and functional evaluation according to the AOFAS scale and radiographic evaluation. Results: The mean age of the patients was 47.3 years, nine men and one woman. According to Gustilo Anderson’s classification, eight cases were grade IIIA and two grade II; in Sanders’ classification, four were type II and six were type III. No case evolved with chronic osteomyelitis or required amputation. After a mean 31.3 months follow-up, all fractures showed consolidation in the radiographic evaluation, with a mean Bohler angle of 4.1 degrees. According to the AOFAS scale, the mean value was 77.7 in the functional evaluation. Conclusion: Open calcaneal fractures with medial wound are often treated in a non-standard manner. The functional and radiographic results followed the high variability of the treatments performed. Level of Evidence IV; Cases series; Retrospective Study.